2023
DOI: 10.1021/acs.inorgchem.3c02698
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategy of the MnOx Catalyst for SCR of NO with NH3: Mechanism of Lead Poisoning and Improvement Method

Hongli Wu,
Weizao Liu,
Ya Liang
et al.

Abstract: The conventional Mn-based catalysts suffer from lead toxicity and require other transition-metal oxides to enhance their resistance in the selective catalytic reduction of NOx with ammonia (NH3-SCR). Herein, we found that the incorporation of inert silica into pure MnOx effectively improved the Pb resistance. The NOx conversion of the MnOx-SiO2-Pb catalyst was nearly 55% higher than that of the MnOx-Pb catalyst, exhibiting enhanced activity at lower temperatures (150–225 °C). To reveal the essential roles at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The redox capacity of the four catalysts was further investigated by the H 2 -TPR. As shown in Figure C, only a wide reduction peak could be observed on the MnOx precursor between 200 and 500 °C, which was attributed to the continuous reduction of MnO 2 to Mn 3 O 4 and MnO with the increase of temperature. After being modified by ligands and calcined in NH 3 atmosphere, the reduction peak of MnOx-350-NH 3 shifted to 537 °C, resulting from the reduction of Mn 3 O 4 to MnO, indicating its weakened redox ability caused by the reduction of Mn 4+ to Mn 3+ in NH 3 atmosphere . When calcined in air atmosphere, MnOx-350-air catalysts displayed two obvious reduction peaks at 309 and 438 °C, which were attributable to the reduction of MnO 2 to Mn 3 O 4 and the simultaneous reduction of Mn 3 O 4 to MnO, respectively. , The phenomenon indicated that the introduction of air was conducive to the formation of Mn 4+ and Mn 3+ , thus improving the redox ability of the catalyst.…”
Section: Resultsmentioning
confidence: 98%
“…The redox capacity of the four catalysts was further investigated by the H 2 -TPR. As shown in Figure C, only a wide reduction peak could be observed on the MnOx precursor between 200 and 500 °C, which was attributed to the continuous reduction of MnO 2 to Mn 3 O 4 and MnO with the increase of temperature. After being modified by ligands and calcined in NH 3 atmosphere, the reduction peak of MnOx-350-NH 3 shifted to 537 °C, resulting from the reduction of Mn 3 O 4 to MnO, indicating its weakened redox ability caused by the reduction of Mn 4+ to Mn 3+ in NH 3 atmosphere . When calcined in air atmosphere, MnOx-350-air catalysts displayed two obvious reduction peaks at 309 and 438 °C, which were attributable to the reduction of MnO 2 to Mn 3 O 4 and the simultaneous reduction of Mn 3 O 4 to MnO, respectively. , The phenomenon indicated that the introduction of air was conducive to the formation of Mn 4+ and Mn 3+ , thus improving the redox ability of the catalyst.…”
Section: Resultsmentioning
confidence: 98%